2011
DOI: 10.1038/labinvest.2010.192
|View full text |Cite|
|
Sign up to set email alerts
|

TNF gene cluster deletion abolishes lipopolysaccharide-mediated sensitization of the neonatal brain to hypoxic ischemic insult

Abstract: In the current study, we explored the role of TNF cluster cytokines on the lipopolysaccharide (LPS)-mediated, synergistic increase in brain injury after hypoxic ischemic insult in postnatal day 7 mice. Pretreatment with moderate doses of LPS (0.3 mg/g) resulted in particularly pronounced synergistic injury within 12 h. Systemic application of LPS alone resulted in a strong upregulation of inflammation-associated cytokines TNFa, LTb, interleukin (IL) 1b, IL6, chemokines, such as CXCL1, and adhesion molecules E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 77 publications
1
56
0
Order By: Relevance
“…The combined exposure to perinatal inflammation and neonatal HI results in a complex interplay of various signaling pathways of which the exact underlying mechanism has not been elucidated yet. Experimental peripheral inflammation induced by LPS is known to induce an inflammatory cerebral state leading to sensitization of the brain to HI injury [15,16,19,21,36,37]. Possible mechanisms via which peripheral LPS can sensitize the brain have been described extensively and consist of: (i) stimulation of endothelial cells of the blood-brain barrier (BBB), (ii) activation/priming of microglia via immune signals produced by endothelial and choroid plexus cells at the level of the BBB, (iii) direct transport of peripheral inflammatory molecules across the BBB, (iv) increased permeability of the BBB, which enhances the influx of peripheral immune cells into the brain, (v) stimulation of the vagal nerve by peripheral cytokines leading to signaling in the brain and (vi) the effects of inflammation on G-protein-coupled receptor signaling in the brain [17,38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combined exposure to perinatal inflammation and neonatal HI results in a complex interplay of various signaling pathways of which the exact underlying mechanism has not been elucidated yet. Experimental peripheral inflammation induced by LPS is known to induce an inflammatory cerebral state leading to sensitization of the brain to HI injury [15,16,19,21,36,37]. Possible mechanisms via which peripheral LPS can sensitize the brain have been described extensively and consist of: (i) stimulation of endothelial cells of the blood-brain barrier (BBB), (ii) activation/priming of microglia via immune signals produced by endothelial and choroid plexus cells at the level of the BBB, (iii) direct transport of peripheral inflammatory molecules across the BBB, (iv) increased permeability of the BBB, which enhances the influx of peripheral immune cells into the brain, (v) stimulation of the vagal nerve by peripheral cytokines leading to signaling in the brain and (vi) the effects of inflammation on G-protein-coupled receptor signaling in the brain [17,38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We showed earlier that HI-induced changes in cytokine mRNA levels were related to changes in the protein levels of these cytokines [71]. Besides the effect on oligodendrocytes, Kendall et al [16] showed that TNF-α is a key factor in the LPS-mediated sensitizing effect on HI brain damage, since deletion of the TNF gene cluster prevented the LPS-induced increase in endothelial and microglia activation and the increase in HI brain damage. Consequently, anti-TNF therapies could be promising in neonates in whom inflammation precedes HI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandins may also be important in LPS-induced brain damage, as injury is associated with an increase in COX-2. 66 Furthermore, both IL-1b 67 and TNFa 68 have been implicated as possible mediators of LPS-induced damage. Recent data also support an important role for microglial recruitment and activation, as well as a role for early neutrophil infiltration, in this neuroinflammatory milieu.…”
Section: Prostaglandins/cyclooxygenase-2mentioning
confidence: 99%
“…91 Moreover, deletion of the TNF gene cluster abolishes LPS-mediated sensitization of the neonatal brain to a hypoxic-ischaemic insult. 68 TNFa treatment is toxic to oligodendrocyte precursors 92 and potentiates IFNc-induced toxicity to these cells in vitro. 93 TNFa also stimulates proliferation, and potentiates the activation of astrocytes 94 and microglia.…”
Section: Death Receptorsmentioning
confidence: 99%